(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
The article deals with the peculiarities of lexical stylistic devices in English language. The actuality of which is directed to define the features of lexical stylistic devices and their usage in modern linguistics. The penetration of modern technology which is called “innovation” accelerates the pace of our life. That requires some changes in science such as the creation of new textbooks, dictionaries and manuals. In order to fulfill these goals one must know every field of linguistics. Due to this task the article puts the aim of analyzing lexical stylistic devices in English language. It is concluded that the lexical stylistic devices in language can be a subject to investigate in different aspects. It’s defined by the final concrete results